THE NOBLE EIGHTFOLD PATH CONCEPTUALIZATION FOR PEACEFUL WORLD - Payogo, PhrapaladSomchai (Journal of Buddhist Education and Research (JBER), 2018)
This article aims to study the perspective of the Noble Eightfold Path, as a guide to peace. Buddhism has been celebrated as a religion of peace. This Eightfold Path is the path through which each individual can do in daily life regardless of their beliefs, traditions, or religions. Actually, we already exercise one or many of these principles from the Noble Eightfold Part in our everyday lives. In its social dimension, the Eightfold Path also coversthe aspect of togetherness to attain peace in life and socials. Buddhists, their role in the establishment of universal peace is concerned and the fundamental principle of Buddhism is to direct the people from the path of destruction to the path of peace. This article concludes the Buddhist worldview is surprisingly in accordance with the insights of peace studies, its insistence on peace by peaceful means and a vital role in the efforts of bringing the culture of peace into existence around the world.